A graphite negative electrode material with good stability and its preparation method and application
By using melamine resin sponge framework and modified polymer treatment in graphite electrodes, the problems of volume change, electrolyte decomposition and lithium ion conduction efficiency in lithium-ion batteries are solved, and the stability of the battery is significantly improved and performance.
Patent Information
- Application Number
- CN202411442412.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-16
AI Technical Summary
Traditional graphite electrodes have problems such as volume changes, electrolyte decomposition, lithium loss and insufficient lithium ion conduction efficiency in lithium-ion batteries, which affect the cycling stability and performance of the battery.
The melamine resin sponge is used as the electrode framework for carbonization, and the graphite is surface treated with modified polymer to form a stable solid electrolyte interface film and improve lithium ion conduction efficiency.
Effectively buffer volume changes, reduce electrolyte decomposition, improve the storage and migration speed of lithium ions, improve the first-time Coulomb efficiency and reversible capacity of the battery, and extend the battery life.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of graphite negative electrode material preparation, in particular to a graphite negative electrode material with good stability and a preparation method and application thereof. Background Art
[0002] In the field of electrochemical energy storage and conversion, graphite electrodes have always been a hot topic of research and application due to their unique physical and chemical properties. Graphite is a layered carbon material with weak van der Waals forces connecting its layers, allowing lithium ions to be easily embedded and removed between layers. This property gives graphite great potential as a negative electrode material for lithium-ion batteries. However, with the growing demand for high-energy density and long-cycle life batteries, the performance bottleneck of traditional graphite electrodes has gradually emerged, prompting researchers to continuously explore the modification and new structural design of graphite electrodes.
[0003] However, traditional graphite electrodes have certain limitations: 1. Volume change: During the charge and discharge process, the insertion and extraction of lithium ions will cause changes in the spacing between graphite layers, which in turn causes the volume expansion and contraction of the electrode material. This volume change will not only affect the cycle stability of the battery, but may also damage the electrode structure and shorten the battery life. 2. Electrolyte decomposition and lithium loss: Direct contact between the graphite electrode surface and the electrolyte often leads to the decomposition of the electrolyte and the loss of lithium ions. This not only reduces the coulombic efficiency of the battery, but also increases the internal resistance of the battery, affecting battery performance. 3. Lithium ion conduction efficiency: The lithium ion conduction efficiency of traditional graphite electrodes is limited by their own physical and chemical properties, and it is difficult to meet the needs of high power density batteries. Summary of the invention
[0004] The purpose of the present invention is to provide a graphite negative electrode material with good stability and a preparation method and application thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A method for preparing a graphite negative electrode material with good stability comprises the following preparation steps:
[0007] S1. Wash the melamine resin sponge with deionized water and anhydrous ethanol alternately for 3 to 4 times, dry it at 105°C for 24 to 26 hours, place it in an argon protective atmosphere, heat it to 900 to 1200°C at 5°C / min, and then carbonize it at high temperature for 1.5 to 2.5 hours to obtain melamine resin sponge carbon;
[0008] S2, adding the modified polymer to deionized water with a mass of 350-380 times the mass of the modified polymer, ultrasonically dispersing for 15-20 minutes, then adding graphite with a mass of 30-35 times the mass of the modified polymer, and then adding anhydrous ethanol with a mass of 40-45 times the mass of the modified polymer, stirring for 30-35 minutes, drying at a temperature of 100-110° C. for 12-14 hours, sintering in a nitrogen atmosphere after drying, with a heating rate of 5° C. / min, a holding temperature of 400-420° C., a holding time of 5-6 hours, cooling to 25-30° C. after the holding is completed, and taking out to obtain modified graphite;
[0009] S3. Add the modified graphite to a sodium carboxymethyl cellulose solution with a mass of 1000-1200 times that of the modified graphite, and prepare a graphite dispersion after ultrasonic dispersion for 10-15 minutes; add the melamine resin sponge carbon to a graphite dispersion with a mass of 100-120 times that of the melamine resin sponge carbon, dry it at a temperature of 100-110°C for 24-26 hours, and then carbonize it at a temperature of 1300-1400°C for 2-2.5 hours under argon protection to obtain a graphite negative electrode material.
[0010] As an optimization, the mass fraction of the sodium carboxymethyl cellulose solution is 0.1-0.15%.
[0011] As an optimization, the modified polymer includes the following preparation steps: 4-vinylpyridine-2-amine, dimethyldiallyl ammonium chloride and monomer silicone are weighed according to a mass ratio of 10:1~2:0.4~0.5, 4-vinylpyridine-2-amine, dimethyldiallyl ammonium chloride and monomer silicone are added to N, N-dimethylformamide with a mass of 4.5~4.8 times of 4-vinylpyridine-2-amine while nitrogen is introduced, and nitrogen is introduced for 0.5~1h after stirring, and the temperature is raised to 60~70°C after the introduction is completed, and then 0.25%~0.3% of azobisisobutyronitrile solution with a mass of 4-vinylpyridine-2-amine is added, and after stirring, the reaction is carried out for 10~12h, and the solution is cooled to 25~30°C and filtered, and the filtered product is added to acetone with a mass of 40~50 times of the filtered product. After soaking for 30~40min, the filtered product is filtered, and the filtered product is washed and dried to obtain a modified polymer.
[0012] As an optimization, the azobisisobutyronitrile solution includes the following preparation steps: adding azobisisobutyronitrile to N,N-dimethylformamide with a mass 5 to 6 times that of azobisisobutyronitrile, stirring evenly, and preparing an azobisisobutyronitrile solution for standby use.
[0013] As an optimization, the dimethyldiallylammonium chloride is washed with benzene 3 to 4 times and dried before use, and then sealed and stored at low temperature for later use.
[0014] As an optimization, the monomer organic silicon includes the following preparation steps: weighing vinyl tris (2-methoxyethoxy) silane, (3,3,3-trifluoropropyl) trichlorosilane, deionized water and isopropanol according to a mass ratio of 1.6-1.8: 2.7-2.9: 1: 2.2-2.3; after weighing, under nitrogen protection and a temperature of 25-30°C, vinyl tris (2-methoxyethoxy) silane and (3,3,3-trifluoropropyl) trichlorosilane are added Add it into deionized water, stir it evenly, and then add isopropanol at a uniform speed within 30-35 minutes. Nitrogen is continuously introduced during the dropping process, and the mixture is stirred for 12-14 hours after the dropping is completed. After the stirring stops, the product is washed with deionized water for 3-4 times, and then a molecular sieve with a mass of 0.075-0.095 times that of isopropanol is added and allowed to stand for 12-14 hours. After that, the fraction with a pressure of 0.4-0.45 kPa and a temperature of 130-135°C is collected by rectification to obtain monomer silicone.
[0015] As an optimization, the pore size of the molecular sieve is 0.5~0.57nm.
[0016] A graphite negative electrode material with good stability is prepared by any of the preparation methods described above.
[0017] Application of the graphite negative electrode material with good stability as described above in lithium-ion batteries.
[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0019] The present application uses melamine resin sponge as the basic skeleton of the electrode. After carbonization, this skeleton has a stable three-dimensional network structure, and its unique spatial morphology can effectively buffer the volume change experienced by the modified graphite during the battery charging and discharging process. In addition, the appropriate carbon layer spacing of the melamine resin sponge and the three-dimensional buffer network work together to ensure that the modified graphite can fully contact the electrolyte, thereby improving the overall performance of the battery.
[0020] In order to reduce the direct interaction between modified graphite and electrolyte, and thus reduce the decomposition of electrolyte and the accompanying lithium loss, this application uses a specially prepared modified polymer to treat the graphite surface. This modified polymer pre-forms a stable solid electrolyte interface film (SEI film) on the graphite surface, effectively isolating the direct contact between graphite and electrolyte, and significantly improving the first coulomb efficiency of the battery.
[0021] In the preparation process of the modified polymer, 4-vinylpyridine-2-amine, dimethyldiallylammonium chloride and fluorine-rich monomer silicone are cleverly combined for copolymerization. Among them, the doping of fluorine and nitrogen not only promotes the transfer of electrons and the conduction efficiency of lithium ions, but also significantly increases the lithium storage active sites on the graphite surface and appropriately expands the interlayer spacing of graphite, thereby greatly improving the storage and migration speed of lithium ions and effectively improving the reversible capacity of the battery.
[0022] On the other hand, the addition of dimethyldiallylammonium chloride, on the one hand, improves the hydrophilicity and dispersibility of the modified polymer, thereby promoting its close contact with graphite; on the other hand, the quaternary ammonium salt groups it contains provide the polymer with high charge density and stable adsorption groups, further enhancing the binding force between the polymer and graphite, and ensuring the stability and reliability of the electrode structure. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0024] In order to more clearly illustrate the method provided by the present invention, the following examples are provided in detail. The raw materials used in the experimental part of the following examples are as follows:
[0025] Table 1 - Raw materials used in the experimental part
[0026] name Specification factory Sodium Carboxymethyl Cellulose Battery Level Qingdao Tianya Chemical Co., Ltd. graphite Analytical grade Shanghai Aladdin Biochemical Technology Co., Ltd. Example 1
[0027] S1. Monomer silicone includes the following preparation steps: the pore size of the molecular sieve is 0.5 nm; vinyl tri(2-methoxyethoxy)silane, (3,3,3-trifluoropropyl)trichlorosilane, deionized water and isopropanol are weighed according to the mass ratio of 1.6:2.7:1:2.2; after weighing, under nitrogen protection and at a temperature of 25°C, vinyl tri(2-methoxyethoxy)silane and (3,3,3-trifluoropropyl)trichlorosilane are added to deionized water, stirred evenly, and isopropanol is added dropwise at a uniform speed within 30 minutes, nitrogen is continuously introduced during the dropping process, and stirred for 12 hours after the dropping is completed. After the stirring stops, the product is washed with deionized water for 3 times, and then a molecular sieve with a mass of 0.075 times that of the isopropanol is added and allowed to stand for 12 hours, and then the fraction with a pressure of 0.4 kpa and a temperature of 130°C is collected by distillation to obtain monomer silicone.
[0028] S2. The modified polymer includes the following preparation steps: adding azobisisobutyronitrile to N,N-dimethylformamide with a mass of 5 times that of azobisisobutyronitrile, stirring evenly, and preparing an azobisisobutyronitrile solution for use; dimethyldiallyl ammonium chloride is washed with benzene three times and dried before use, and then sealed and stored at low temperature for use; 4-vinylpyridine-2-amine, dimethyldiallyl ammonium chloride and monomer silicone are weighed in a mass ratio of 10:1:0.4, and 4-vinylpyridine-2-amine and dimethyldiallyl ammonium chloride are added while nitrogen is introduced. and monomer silicone are added to N, N-dimethylformamide with a mass of 4.5 times that of 4-vinylpyridine-2-amine, stirred evenly, and then nitrogen is introduced for 0.5h. After the introduction is completed, the temperature is raised to 60°C, and then azobisisobutyronitrile solution with a mass of 0.25% times that of 4-vinylpyridine-2-amine is added, stirred evenly, reacted for 10h, cooled to 25°C and filtered, the filtered product is added to acetone with a mass of 40 times that of the filtered product, soaked for 30min and then filtered, the filtered product is washed and dried to obtain a modified polymer.
[0029] S3, washing the melamine resin sponge with deionized water and anhydrous ethanol alternately for 3 times, drying it at 100°C for 24 hours, taking it out, placing the dried melamine resin sponge in an argon protection atmosphere, heating it to 900°C at 5°C / min, and then high-temperature carbonizing it for 1.5 hours to obtain melamine resin sponge carbon;
[0030] S4, adding the modified polymer to deionized water with a mass of 350 times that of the modified polymer, ultrasonically dispersing for 15 minutes, then adding graphite with a mass of 30 times that of the modified polymer, and then adding anhydrous ethanol with a mass of 40 times that of the modified polymer, stirring for 30 minutes, drying at a temperature of 100°C for 12 hours, sintering in a nitrogen atmosphere after drying, with a heating rate of 5°C / min, a heat preservation temperature of 400°C, a heat preservation time of 5 hours, cooling to 25°C after the heat preservation is completed, and taking out to obtain modified graphite;
[0031] S5. Add the modified graphite to a 0.1% sodium carboxymethyl cellulose solution with a mass fraction of 1000 times the mass of the modified graphite, and ultrasonically disperse it for 10 minutes to prepare a graphite dispersion. Add the melamine resin sponge carbon to a graphite dispersion with a mass of 100 times the mass of the melamine resin sponge carbon, dry it at a temperature of 100°C for 24 hours, and then carbonize it at a temperature of 1300°C for 2 hours under argon protection to obtain a graphite negative electrode material. Example 2
[0032] S1. The monomer silicone comprises the following preparation steps: the pore size of the molecular sieve is 0.53 nm; vinyl tri(2-methoxyethoxy)silane, (3,3,3-trifluoropropyl)trichlorosilane, deionized water and isopropanol are weighed in a mass ratio of 1.7:2.8:1:2.2; after weighing, under nitrogen protection and at a temperature of 30°C, vinyl tri(2-methoxyethoxy)silane and (3,3,3-trifluoropropyl)trichlorosilane are added to deionized water, stirred evenly, and isopropanol is added dropwise at a uniform speed within 35 minutes, nitrogen is continuously introduced during the dropping process, and the mixture is stirred for 13 hours after the dropping is completed. After the stirring stops, the product is washed with deionized water for 3 times, and a molecular sieve with a mass of 0.085 times that of the isopropanol is added and allowed to stand for 13 hours, and then the fraction with a pressure of 0.42 kpa and a temperature of 130°C is collected by rectification to obtain the monomer silicone.
[0033] S2. The modified polymer includes the following preparation steps: adding azobisisobutyronitrile to N,N-dimethylformamide with a mass of 5 times that of azobisisobutyronitrile, stirring evenly, and preparing an azobisisobutyronitrile solution for use; washing dimethyldiallyl ammonium chloride with benzene three times before use, drying, and sealing and storing at low temperature for use; weighing 4-vinylpyridine-2-amine, dimethyldiallyl ammonium chloride and monomer silicone in a mass ratio of 10:1.5:0.45, and adding 4-vinylpyridine-2-amine, dimethyldiallyl ammonium chloride and monomer silicone in a mass ratio of 10:1.5:0.45, and introducing nitrogen while Ammonia and monomer silicone are added to N, N-dimethylformamide with a mass of 4.7 times that of 4-vinylpyridine-2-amine, stirred evenly, and then nitrogen is introduced for 0.5h. After the introduction is completed, the temperature is raised to 65°C, and then azobisisobutyronitrile solution with a mass of 0.25% times that of 4-vinylpyridine-2-amine is added, stirred evenly, reacted for 11h, cooled to 25°C and filtered, the filtered product is added to acetone with a mass of 45 times that of the filtered product, soaked for 35min and then filtered, the filtered product is washed and dried to obtain a modified polymer.
[0034] S3, washing the melamine resin sponge with deionized water and anhydrous ethanol alternately for 3 times, drying it at 105°C for 25 hours, taking it out, placing the dried melamine resin sponge in an argon protection atmosphere, heating it to 1000°C at 5°C / min, and then high-temperature carbonizing it for 2 hours to obtain melamine resin sponge carbon;
[0035] S4, adding the modified polymer to deionized water 360 times the mass of the modified polymer, ultrasonically dispersing for 18 minutes, then adding graphite 34 times the mass of the modified polymer, and then adding anhydrous ethanol 42 times the mass of the modified polymer, stirring for 33 minutes, drying at 105°C for 13 hours, sintering in a nitrogen atmosphere after drying, with a heating rate of 5°C / min, a holding temperature of 410°C, a holding time of 5.5 hours, cooling to 25°C after the holding is completed, and taking out to obtain modified graphite;
[0036] S5. Add the modified graphite to a 0.1% sodium carboxymethyl cellulose solution with a mass fraction of 1100 times the mass of the modified graphite, and ultrasonically disperse it for 12 minutes to prepare a graphite dispersion. Add the melamine resin sponge carbon to a graphite dispersion with a mass of 110 times the mass of the melamine resin sponge carbon, dry it at a temperature of 105°C for 25 hours, and then carbonize it at a temperature of 1350°C for 2 hours under argon protection to obtain a graphite negative electrode material. Example 3
[0037] S1. Monomer silicone includes the following preparation steps: the pore size of the molecular sieve is 0.57 nm; vinyl tri(2-methoxyethoxy)silane, (3,3,3-trifluoropropyl)trichlorosilane, deionized water and isopropanol are weighed in a mass ratio of 1.8:2.9:1:2.3; after weighing, under nitrogen protection and at a temperature of 30°C, vinyl tri(2-methoxyethoxy)silane and (3,3,3-trifluoropropyl)trichlorosilane are added to deionized water, stirred evenly, and isopropanol is added dropwise at a uniform speed within 35 minutes, nitrogen is continuously introduced during the dropping process, and the mixture is stirred for 14 hours after the dropping is completed. After the stirring stops, the product is washed with deionized water for 4 times, and a molecular sieve with a mass of 0.095 times that of the isopropanol is added and allowed to stand for 14 hours, and then the fraction with a pressure of 0.45 kpa and a temperature of 135°C is collected by rectification to obtain monomer silicone.
[0038] S2. The modified polymer includes the following preparation steps: adding azobisisobutyronitrile to N,N-dimethylformamide (6 times the mass of azobisisobutyronitrile), stirring evenly, and preparing an azobisisobutyronitrile solution for use; washing dimethyldiallyl ammonium chloride with benzene for 4 times before use, drying, and sealing and storing at low temperature for use; weighing 4-vinylpyridine-2-amine, dimethyldiallyl ammonium chloride and monomer silicone in a mass ratio of 10:2:0.5, and adding 4-vinylpyridine-2-amine, dimethyldiallyl ammonium chloride and monomer silicone in a mass ratio of 10:2:0.5, and introducing nitrogen while mixing 4-vinylpyridine-2-amine, dimethyldiallyl ammonium chloride and monomer silicone. Ammonia and monomer silicone are added to N, N-dimethylformamide with a mass of 4.8 times that of 4-vinylpyridine-2-amine, stirred evenly, and then nitrogen is introduced for 1 hour. After the introduction is completed, the temperature is raised to 70°C, and then azobisisobutyronitrile solution with a mass of 0.3% times that of 4-vinylpyridine-2-amine is added, stirred evenly, reacted for 12 hours, cooled to 30°C and filtered, the filtered product is added to acetone with a mass of 50 times that of the filtered product, soaked for 40 minutes and then filtered, the filtered product is washed and dried to obtain a modified polymer.
[0039] S3, washing the melamine resin sponge with deionized water and anhydrous ethanol alternately for 4 times, drying it at 110°C for 26 hours, taking it out, placing the dried melamine resin sponge in an argon protection atmosphere, heating it to 1200°C at 5°C / min, and then high-temperature carbonizing it for 2.5 hours to obtain melamine resin sponge carbon;
[0040] S4, adding the modified polymer to deionized water with a mass of 380 times that of the modified polymer, ultrasonically dispersing for 20 minutes, then adding graphite with a mass of 35 times that of the modified polymer, and then adding anhydrous ethanol with a mass of 45 times that of the modified polymer, stirring for 5 minutes, drying at a temperature of 110°C for 14 hours, sintering in a nitrogen atmosphere after drying, with a heating rate of 5°C / min, a heat preservation temperature of 420°C, a heat preservation time of 5-6 hours, cooling to 30°C after the heat preservation, and obtaining modified graphite;
[0041] S5. Add the modified graphite to a 0.15% sodium carboxymethyl cellulose solution with a mass fraction of 1200 times the mass of the modified graphite, and ultrasonically disperse it for 15 minutes to prepare a graphite dispersion. Add the melamine resin sponge carbon to a graphite dispersion with a mass of 120 times the mass of the melamine resin sponge carbon, dry it at a temperature of 110°C for 26 hours, and then carbonize it at a temperature of 1400°C for 2.5 hours under argon protection to obtain a graphite negative electrode material. Example 4
[0042] The only difference from Example 2 is that in step S2, the "monomer silicone" is replaced by "vinyl tris(2-methoxyethoxy)silane". Example 5
[0043] The only difference from Example 2 is that step S2: the modified polymer includes the following preparation steps: adding azobisisobutyronitrile to N,N-dimethylformamide with a mass of 5 times that of azobisisobutyronitrile, stirring evenly, and preparing an azobisisobutyronitrile solution for standby use; dimethyldiallyl ammonium chloride is washed with benzene three times and dried before use, and then sealed and stored at low temperature for standby use; 4-vinylpyridine-2-amine and dimethyldiallyl ammonium chloride are weighed in a mass ratio of 10:1.5, and 4-vinylpyridine-2-amine and dimethyldiallyl ammonium chloride are added while nitrogen is introduced. Allyl ammonium chloride was added to N, N-dimethylformamide (4.7 times the mass of 4-vinylpyridine-2-amine), and nitrogen was introduced for 0.5 h after stirring. After the introduction was completed, the temperature was raised to 65°C, and then azobisisobutyronitrile solution (0.25% times the mass of 4-vinylpyridine-2-amine) was added. After stirring, the mixture was reacted for 11 h, cooled to 25°C, and filtered. The filtered product was added to acetone (45 times the mass of the filtered product), soaked for 35 min, and then filtered. The filtered product was washed and dried to obtain a modified polymer. Example 6
[0044] The only difference from Example 2 is that in step S4, the "modified polymer" is replaced by "4-vinylpyridine-2-amine".
[0045] Test Example 1
[0046] Electrochemical performance test:
[0047] The graphite negative electrode materials prepared in the above Examples 1 to 6 were cut into pole pieces with a diameter of 8 mm as self-supporting electrodes, metallic lithium was used as the counter electrode, KFSI / DME electrolyte was used as the electrolyte, and a glass fiber separator was used to assemble into a CR2025 button half-cell in an argon atmosphere glove box;
[0048] Constant current charge and discharge test: The composite electrode was subjected to constant current charge and discharge test at a rate of 0.1C, and the reversible capacity after 100 cycles was measured. The capacity retention rate was calculated by the reversible capacity after 100 cycles and the reversible capacity of the first cycle; capacity retention rate = reversible capacity after 100 cycles / reversible capacity of the first cycle*100%. The specific test results are shown in Table 2 below;
[0049] Table 2 Constant current charge and discharge test results
[0050] Sample <![CDATA[Initial reversible capacity / mAh g -1 > First coulombic efficiency / % Capacity retention rate / % Example 1 313.8 67.8 92.4 Example 2 312.9 68.1 91.3 Example 3 313.2 67.3 91.8 Example 4 253.8 66.5 92.5 Example 5 223.7 57.6 82.3 Example 6 213.7 52.8 81.4
[0051] From the comparison of the experimental data of Examples 1 to 3 in Table 2, it can be found that the maximum first-cycle reversible capacity of the graphite negative electrode material prepared by the present invention reaches 313.8 mAh g -1 The maximum first coulombic efficiency is 68.1%, which shows that the graphite negative electrode material has good lithium storage performance and still maintains good performance after repeated use;
[0052] In Example 4, the first-cycle reversible capacity is greatly reduced, mainly because (3,3,3-trifluoropropyl)trichlorosilane is not used to modify the organosilicon monomer, resulting in only nitrogen in the final modified polymer, which leads to a decrease in the final active site and a decrease in its lithium storage function. However, its first coulombic efficiency and capacity retention rate are both excellent. It is speculated that this is because the unmodified organosilicon monomer used does not contain fluorine, which increases its hydrophilicity and dispersibility, and is in closer contact with graphite, resulting in good performance of its first coulombic efficiency and capacity retention rate.
[0053] In Examples 5 and 6, the decrease in the first-cycle reversible capacity and the first coulombic efficiency is mainly due to the fact that no silicone monomer is used for copolymerization and only 4-vinylpyridine-2-amine is used, which reduces the hydrophilicity of the final modified polymer, resulting in a decrease in the final graphite surface film formation and the number of active sites thereon, thus leading to poor final results.
[0054] And from the capacity after the above-mentioned cyclic charge and discharge test, it can be seen that due to the use of melamine resin sponge and graphite for compounding, the capacity retention rate remains good, with the lowest being 81.4%. This is because the carbon network structure of the melamine resin sponge itself is structurally stable and can inhibit the volume expansion of the graphite negative electrode. The modified graphite has more active sites, which gives it good lithium storage performance.
[0055] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing a graphite negative electrode material with good stability, characterized in that: The method comprises the following preparation steps: S1. Wash the melamine resin sponge with deionized water and anhydrous ethanol alternately for 3 to 4 times, dry it at 100 to 110°C for 24 to 26 hours, place it in an argon protective atmosphere, heat it to 900 to 1200°C at 5°C / min, and then carbonize it at high temperature for 1.5 to 2.5 hours to obtain melamine resin sponge carbon; S2, adding the modified polymer to deionized water with a mass of 350-380 times the mass of the modified polymer, ultrasonically dispersing for 15-20 minutes, then adding graphite with a mass of 30-35 times the mass of the modified polymer, and then adding anhydrous ethanol with a mass of 40-45 times the mass of the modified polymer, stirring for 30-35 minutes, drying at a temperature of 100-110° C. for 12-14 hours, sintering in a nitrogen atmosphere after drying, with a heating rate of 5° C. / min, a holding temperature of 400-420° C., a holding time of 5-6 hours, cooling to 25-30° C. after the holding is completed, and taking out to obtain modified graphite; S3. Add the modified graphite to a sodium carboxymethyl cellulose solution with a mass of 1000-1200 times that of the modified graphite, and prepare a graphite dispersion after ultrasonic dispersion for 10-15 minutes; add the melamine resin sponge carbon to a graphite dispersion with a mass of 100-120 times that of the melamine resin sponge carbon, dry it at a temperature of 100-110°C for 24-26 hours, and then carbonize it at a temperature of 1300-1400°C for 2-2.5 hours under argon protection to obtain a graphite negative electrode material.
2. The method for preparing a graphite negative electrode material with good stability according to claim 1, characterized in that: The mass fraction of the sodium carboxymethyl cellulose solution is 0.1-0.15%.
3. The method for preparing a graphite negative electrode material with good stability according to claim 1, characterized in that: The modified polymer comprises the following preparation steps: 4-vinylpyridine-2-amine, dimethyldiallyl ammonium chloride and monomer organosilicon are weighed in a mass ratio of 10:1-2:0.4-0.5, 4-vinylpyridine-2-amine, dimethyldiallyl ammonium chloride and monomer organosilicon are added to N, N-dimethylformamide with a mass of 4.5-4.8 times of 4-vinylpyridine-2-amine while nitrogen is introduced, stirring evenly and then introducing nitrogen for 0.5-1h, heating to 60-70°C after the introduction is completed, then adding azobisisobutyronitrile solution with a mass of 0.25%-0.3% times of 4-vinylpyridine-2-amine, stirring evenly, reacting for 10-12h, cooling to 25-30°C and filtering, adding the filtered product to acetone with a mass of 40-50 times of the filtered product, soaking for 30-40min and then filtering, washing and drying the filtered product to obtain the modified polymer.
4. The method for preparing a graphite negative electrode material with good stability according to claim 3, characterized in that: The azobisisobutyronitrile solution comprises the following preparation steps: adding azobisisobutyronitrile to N,N-dimethylformamide with a mass 5 to 6 times of the azobisisobutyronitrile, stirring evenly, and preparing the azobisisobutyronitrile solution for standby use.
5. The method for preparing a graphite negative electrode material with good stability according to claim 3, characterized in that: The dimethyldiallylammonium chloride is washed with benzene 3-4 times before use, dried, and then sealed and stored at low temperature for later use.
6. The method for preparing a graphite negative electrode material with good stability according to claim 3, characterized in that: The monomer organic silicon comprises the following preparation steps: weighing vinyl tris (2-methoxyethoxy) silane, (3,3,3-trifluoropropyl) trichlorosilane, deionized water and isopropanol according to a mass ratio of 1.6-1.8: 2.7-2.9: 1: 2.2-2.3; after weighing, adding vinyl tris (2-methoxyethoxy) silane and (3,3,3-trifluoropropyl) trichlorosilane to the deionized water under nitrogen protection and a temperature of 25-30°C; After stirring evenly in deionized water, isopropanol is uniformly added dropwise within 30-35 minutes, nitrogen is continuously introduced during the dropping process, and the mixture is stirred for 12-14 hours after the dropping is completed. After the stirring stops, the product is washed with deionized water for 3-4 times, and then a molecular sieve with a mass of 0.075-0.095 times that of isopropanol is added and allowed to stand for 12-14 hours. After that, the fraction with a pressure of 0.4-0.45 kPa and a temperature of 130-135°C is collected by rectification to obtain monomer silicone.
7. The method for preparing a graphite negative electrode material with good stability according to claim 6, characterized in that: The pore size of the molecular sieve is 0.5-0.57 nm.
8. A graphite negative electrode material with good stability, characterized in that: The method is prepared according to any one of claims 1 to 7.
9. Use of the graphite negative electrode material with good stability as claimed in claim 8 in a lithium ion battery.
Citation Information
Patent Citations
Preparation method of graphene-polyaniline composite sponge
CN109233273A
Preparation and characterization method of graphene composite sponge
CN110627045A